Simvastatin Toxicity Induces Mitochondrial Dysfunction in Rat Skeletal Muscle - Zulfahmidah; Marhaen Hardjo; Syahrijuita Kadir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Statins are the class of drugs that are widely used for lowering LDL cholesterol and as primary and secondary prevention to cardiovascular disease. However, the widespread use of statins is constrained by the presence of toxicity or intolerance, which affects drug control rates. The toxicity or intolerance of statins ranges from 10-15%. The most common statin toxicity is statin-associated muscle symptoms (SAMS). The underlying mechanisms of SAMS involve the disruption of mitochondrial biogenesis, potential membrane changes, reduced number of mitochondria, and changes in protein oxidative activity due to the accumulation of ROS in cells and tissues. The disruption of mitochondrial biogenesis can be marked by a decrease of peroxisome proliferator-activated receptor co-activator gamma (PGC-1a). This study aimed to determine the effect of simvastatin on skeletal muscle PGC-1a.Methods: Sixteen female Wistar rats (8-10 weeks of age) were randomized into 2 groups: (1) control group (n=8), and (2) simvastatin group(n=8). For 30 days, the simvastatin group was exposed to simvastatin at a dose of 10 mg/kg/day. Meanwhile, the control group animals only received 0.5% methyl cellulose. Gastrocnemius muscles were collected and PGC-1a levels were evaluated by using ELISA Kit.Results: Following 30 days of treatment, a significantly lower level of skeletal muscle PGC-1awas observed in the simvastatin group compared to the control group (p = .026). Conclusion: Our finding indicates that administration of simvastatin at a dose of 10 mg/kg/day for 30 days may decrease skeletal muscle PGC-1a leading to mitochondrial dysfunction in rat skeletal muscle